Analisis Pendapatan Daerah pada Badan Pengelolaan Keuangan dan Aset Daerah Kota Malang 2018–2023 - Dewi Fatma Nailul Fitroh; Sonnia Dalila Wahida; Novi Khoiriawati; Oktaviana Nadila; Putri Hanidar Nuraini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Regional income is one of the important indicators in assessing the financial performance of local governments, especially in supporting development and public services. Malang City as one of the regions with growing economic dynamics, requires optimal revenue management through the Regional Financial and Asset Management Agency. The purpose of this study is to analyze the structure and trend of local income and evaluate the allocation of regional spending. The method used is quantitative descriptive with data collection through observation of budget realization reports and analysis of revenue trends. The findings of the study indicate a significant increase in local revenue, especially from the hotel, restaurant, and entertainment tax sector, although there are still challenges in managing assets and transfer funds. The implications of the results of this study are expected to contribute to the development of more effective fiscal policies, as well as increasing transparency and accountability in regional financial management in Malang City. This study also provides strategic recommendations for optimizing regional income in the future.